Volumetric Raman chemical imaging of drug delivery systems. (8th March 2020) - Slipets, Roman; Ilchenko, Oleksii; Mazzoni, Chiara; Tentor, Fabio; Nielsen, Line Hagner; Boisen, Anja
Abstract: The ability to image drug distribution inside a several hundred micron thick polymer matrix, encapsulated by a protective coating, would greatly contribute to the understanding of the performance and shortcomings of drug delivery devices. Here, we present an experimental framework for deep volumetric Raman imaging (dVRI), where common challenges such as low Raman cross section, fluorescence, and low transparency of samples are overcome. We apply dVRI to a selection of drug delivery forms, tablets with thin protective coatings and drug‐loaded microdevices. We demonstrate three‐dimensional visualization of the different drug/polymeric materials, constituting a drug delivery device, with imaging depth of 225 μm. Abstract : An experimental framework for deep volumetric Raman imaging (dVRI) is presented. Common challenges such as low Raman cross section, fluorescence, and low transparency of samples are overcome. We apply dVRI to a selection of drug delivery forms, tablets with thin protective coatings and drug‐loaded microdevices and demonstrate 3D visualization of the different drug/polymeric materials, constituting a drug delivery device, with imaging depth of 225 μm.